Faktor – Faktor Yang Berhubungan Dengan Pengeluaran ASI Pada Ibu Post Partum - Sani, Novriyana; Yantina, Yuli; Kurniasari, Devi (MIDWIFERY JOURNAL, 2024)
Back graound Lampung Province health in 2018 the coverage of exclusive breastfeeding was 56.1%, while in 2019 it decreased to 42.7%. The number of post partum mothers at Puri Betik Hati mother and child hospital in February 2020 was 280 post partum mothers, of which 112 mothers (41.2%) had breastfeeding out at 72 hours post partum (breastfeeding was slow), 11 mothers (4%) had more milk. than 72 hours or can be categorized as late, 104 mothers (35.3%) at 48 hours post partum, and 53 mothers (19.5%) breastfeeding out at 24 hours post partum which can be categorized as fast. The purpose of this study was to determine the factors associated with breastfeeding in postpartum mothers at Puri Betik Hati mother and child hospital in 2020. This type of research is quantitative using a cross sectional approach design. The population in this study were all post partum mothers at Puri Betik Hati mother and child hospital, as many as 185 respondents, the sample of all postpartum mothers at the time of the study were 109 respondents, using the sampling technique, namely Accidental Sampling. Based on the results of statistical tests, it was found that there was a relationship between maternal age and breastfeeding with the Chi-Square test p-value of 0.040 ≤ α (0.05) and an OR value of 2.987. There is a relationship between maternal parity on breastfeeding expenditure with the results of the Chi-Square test p-value of 0.000 ≤ α (0.05) and the OR value of 0.155. There is no relationship between maternal occupation and breastfeeding expenditure with the results of the Chi-Square test p-value of 0.395 ≥ α (0.05) and the OR value of 1.417. There is no correlation factor between maternal education and breastfeeding expenditure with the results of the Chi-Square test p-value of 0.452 ≥ α (0.05) and an OR value of 1.607.Conclusion There is a relationship between husband's support for breastfeeding and the results of the Chi-Square test p-value of 0.000 ≤ α (0.05) and the OR value of 0.033. There is no relationship between Early Initiation of Breastfeeding and breastfeeding with the Chi-Square test results p-value of 0.338 ≥ α (0.05) and an OR value of 0.671.Suggestion expected to provide information about the factors associated with breastfeeding in post-partum mothers, that the husbands will continue to provide support to mothers in breastfeeding and reduce anxiety levels in postpartum mothers. Keywords : release of breast milk,postpartum ABSTRAK Latar Belakang Profil data kesehatan Provinsi Lampung pada tahun 2018 cakupan pemberian ASI eksklusif sebesar 56,1% sedangkan pada tahun 2019 mengalami penurunan menjadi 42,7%. Jumlah ibu post partum di RSIA Puri Betik Hati pada bulan Februari 2020 adalah sebanyak 280 ibu post partum, dimana diantaranya 112 ibu (41.2%) ASI keluar pada 72 jam post partum (pengeluaran ASI lambat), 11 ibu (4%) ASI keluar lebih dari 72 jam atau dapat dikategorikan lambat, 104 ibu (35.3%) pada 48 jam post partum, dan 53 ibu (19.5%) ASI keluar pada 24 jam post partum yang dapat dikategorikan cepat.Tujuan dalam penelitian ini adalah diketahui faktor – faktor yang berhubungan dengan pengeluaran ASI pada ibu Post Partum di RSIA Puri Betik Hati Bandar Lampung tahun 2020. Jenis Penelitinan ini adalah kuantitatif dengan menggunakan rancangan pendekatan Cross Sectional. Populasi dalam penelitian ini adalah seluruh ibu post partum di  RSIA Puri Betik Hati yaitu sebanyak 185 responden, sampel seluruh ibu postpartum pada saat penelitian berlangsung sebanyak 109 responden, dengan menggunakan teknik Pengambilan sampel yaitu Accidental Sampling.Hasil Berdasarkan hasil uji statistik, didapatkan bahwa ada hubungan antara Usia ibu terhadap pengeluaran ASI dengan hasil uji Chi-Square p-value sebesar 0,040 ≤ α (0,05) dan nilai OR sebesar 2.987. Ada hubungan antara Paritas ibu terhadap pengeluaran ASI dengan hasil uji Chi-Square p-value sebesar 0,000 ≤ α (0,05) dan nilai OR sebesar 0,155. Tidak Ada hubungan antara Pekerjaan ibu terhadap pengeluaran ASI dengan hasil uji Chi-Square p-value sebesar 0,395 ≥ α (0,05) dan nilai OR sebesar 1.417. Tidak Ada faktor hubungan antara Pendidikan ibu terhadap pengeluaran ASI dengan hasil uji Chi-Square p-value sebesar 0,452 ≥ α (0,05) dan nilai OR sebesar 1.607.Kesimpulan Ada hubungan antara Dukungan Suami terhadap pengeluaran ASI dengan hasil uji Chi-Square p-value sebesar 0,000 ≤ α (0,05) dan nilai OR sebesar 0,033. Tidak Ada hubungan antara Inisiasi Menyusu Dini dengan pengeluaran ASI dengan hasil uji Chi-Square p-value sebesar 0,338 ≥ α (0,05) dan  nilai OR sebesar 0,671.Saran memberikan informasi tentang faktor – faktor yang berhubungan dengan pengeluaran ASI pada ibu post partum, dan diharapkan agar suami untuk tetap memberikan dukungan kepada ibu dalam memberikan ASI dan dapat menurunkan tingkat kecemasan pada ibu postpartum. Kata Kunci : Pengeluaran ASI,Post partum Bakri, I., Sari, M. M., & Pertiwi, F. D. (2019). HUBUNGAN DUKUNGAN SUAMI DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS SEMPUR KOTA BOGOR TAHUN 2018. PROMOTOR, 2(1), 27-36.Hani, R. U. (2014). Hubungan dukungan suami terhadap keberhasilan pemberian Asi eksklusif pada ibu primipara di wilayah kerja puskesmas pisangan.Hartini, S., & Subiyatun, S. (2014). Hubungan Tingkat Pendidikan Ibu dengan Keberhasilan ASI Eksklusif pada Bayi Umur 6-12 Bulan di Puskesmas Kasihan II Yogyakarta (Doctoral dissertation, STIKES'Aisyiyah Yogyakarta).Huang, Y. Y., Lee, J. T., Huang, C. M., & Gau, M. L. (2009). Factors related to maternal perception of milk supply while in the hospital. Journal of Nursing Research, 17(3), 179-188.Infodatin, B. (2018). Pusat Data dan Informasi Kementrian Kesehatan RI,“. Indokator dan Target”, Jakarta.Kusumawardhani. (2010). ASI Bikin Anak Cerdas. Jakarta. Djambatan.Mamonto, T. (2015). Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif Pada Bayi Di Wilayah Kerja Puskesmas Kotobangon Kecamatan Kotamobagu Timur Kota Kotamobagu. KESMAS, 4(1).Mawaddah, S. (2018). Hubungan Inisiasi Menyusu Dini Dengan Pemberian Asi Ekslusif Pada Bayi. Jurnal Info Kesehatan, 16(2), 214-225.Nasihah, L. (2015). Hubungan Tingkat Pendidikan dengan Perilaku Ibu dalam Pemberian Asidi BPM Ny. Andre Kediri. Jurnal Ners dan Kebidanan (Journal of Ners and Midwifery), 2(2), 144-149.Nisman, W. A., Margaretha, E. M., Sandi, A., & Lesmana, S. (2011). Panduan Ibu Pintar Menyusui.Notoatmodjo, S. (2010). Metodologi Penelitian Kesehatan, Rineka Cipta. Jakarta. Indonesia.Nurliawati, E. (2010). Faktor-faktor yang berhubungan dengan produksi air susu ibu pada ibu pasca seksio sesarea di wilayah kota dan kabupaten tasikmalaya. Jurnal FIK UI.Nyqvist, K. H., Häggkvist, A. P., Hansen, M. N., Kylberg, E., Frandsen, A. L., Maastrup, R., ... & Haiek, L. N. (2013). Expansion of the baby-friendly hospital initiative ten steps to successful breastfeeding into neonatal intensive care: expert group recommendations. Journal of Human Lactation, 29(3), 300-309.Ojong, I. N., Uga, A. L., & Chiotu, C. N. (2015). Knowledge and attitude of pregnant women towards focused ante natal care services in university of calabar teaching hospital, calabar, cross river state. Nigeria, 1(1), 14-23.Puspitasari, S., & Pujiastuti, W. (2015). HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP STATUS GIZIPADA BAYI USIA 7-8 BULAN DI WILAYAH PUSKESMAS TLOGOMULYO, KABUPATEN TEMANGGUNG TAHUN 2014. Jurnal Kebidanan, 4(8), 62-69.Rahmawati, A., & Prayogi, B. (2017). Analisis Faktor yang Mempengaruhi Produksi Air Susu Ibu (ASI) pada Ibu Menyusui yang Bekerja. Jurnal Ners dan Kebidanan (Journal of Ners and Midwifery), 4(2), 134-140.Raharjo, B. B. (2014). Profil ibu dan peran bidan dalam praktik inisiasi menyusu dini dan asi eksklusi. KEMAS: Jurnal Kesehatan Masyarakat, 10(1), 53-63.Risneni, A. Y. (2016). Buku Ajar Asuhan Kebidanan Nifas dan Menyusui. Jakarta: Trans Info Media.SDKI. (2017). Survei Demografi Kesehatan Indonesia. JakartaUNICEF, W. (2018). Capture the Moment–Early initiation of breastfeeding: The best start for every newborn. New York: UNICEF.World Health Organization. (2002). The optimal duration of exclusive breastfeeding: a systematic review. In The optimal duration of exclusive breastfeeding: a systematic review.World Health Organization. (2017). Guideline: protecting, promoting and supporting breastfeeding in facilities providing maternity and newborn services (No. 9789241550086). World Health Organization.